Analisis UI/UX Untuk Perancangan Website Apotek dengan Metode Human Centered Design dan System Usability Scale - Cintya Damayanti; Agung Triayudi; Ira Diana Sholihati (STMIK Budi Darma, 2022)
Website based of technology information system widely using by organizations and companies. One of it’s application are inventory on Apotek rakyat anda. Apotek rakyat anda are pharmacy shop who sells medicines. Following the technology growth on the use of database electronic system digital based knowing as application or information system. This system has been made for the user based on user interface and user experience. The used of user interface for fulfing user needs and user experience for success parameter on the system that has been build. Methods for designing are Human-Centered Design (HCD) approach, for knowing system utility are System Usability Scale (SUS) method. Hoping this designing information system will help on inventory on Apotek Rakyat Anda.